2012
DOI: 10.1590/s0034-737x2012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Antibioticoprofilaxia em cirurgias de cães e gatos: necessidade e realidade

Abstract: Antibiotic prophylaxis in surgery of dogs and cats: the necessity and the realityAntimicrobial prophylaxis aim at preventing surgical wound contamination after the exposure to any microorganism and before infection is established. Inhibitory antimicrobial concentrations should be reached and maintained on the incision throughout the entire surgical procedure in order to prevent microbial growth. In veterinary medicine, antimicrobial prophylaxis is clearly disclosure and accepted as an important action to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
2
0
5
Order By: Relevance
“…As enfermidades que levaram às enucleações de bulbo ocular foram devido a traumas, mas com lesões restritas ao órgão, permitindo que os animais fossem classi-ficados como ASA II [2]. Um paciente ASA II submetido à correção de eventração pós-cirúrgica (OSH), apresentou tal eventração por lambedura da ferida cirúrgica (ausência do colar protetor), que é uma das principais causas de complicações pós-operatórias em cães e gatos [4].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As enfermidades que levaram às enucleações de bulbo ocular foram devido a traumas, mas com lesões restritas ao órgão, permitindo que os animais fossem classi-ficados como ASA II [2]. Um paciente ASA II submetido à correção de eventração pós-cirúrgica (OSH), apresentou tal eventração por lambedura da ferida cirúrgica (ausência do colar protetor), que é uma das principais causas de complicações pós-operatórias em cães e gatos [4].…”
Section: Discussionunclassified
“…A obstrução uretral em felinos é uma das doenças com alto percentual de urgências e, se não tratadas em tempo hábil, conduz a complicações graves [23]. Neste estudo, seis gatos com DTUIF obstrutiva, não tratados imediatamente evoluíram para categorias de maior risco anestésico (ASA III e IV), comprovando que tal enfermidade necessita de atendimento rápido [4], pois predispõe à alta mortalidade [27].…”
Section: Discussionunclassified
“…The surgical site infection (SSI) is a common and widespread nosocomial infection in human medicine (Humphreys, 2009) and is considered the most important cause of postoperative complications, contributing significantly to increased morbidity and mortality in these patients (Sitio…, 2009). In the past two decades, this type of infection has become an increasing concern in veterinary hospitals (Braga et al, 2012, Corsini et al, 2014, Murta et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Corsini et al (2014) working in a veterinary hospital found an SSI infection rate of 5.24% and Murta et al (2015) of 3.46%. Most are caused by multiple microorganisms, usually multidrug-resistant (MDR), and have many risk factors (Braga et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A prevenção da infecção representa aspecto determinante para evitar as complicações pós-cirúrgicas (Reis 2014). A administração profilática de antimicrobianos é muito utilizada no controle de infecções cirúrgicas (Braga et al 2012), contudo, o emprego errôneo desses fármacos favoreceu o aparecimento de microrganismos resistentes, diminuindo a eficiência desta prática (Oliveira et al 2011). Assim sendo, a forma mais eficaz de prevenção da infecção cirúrgica é através do uso de uma técnica asséptica rigorosa, que envolve a preparação do paciente, da equipe cirúrgica, esterilização dos equipamentos, preparação das instalações cirúrgicas, emprego de uma técnica operatória adequada e cuidados pós-operatórios (Cockshutt 2007).…”
Section: Introductionunclassified